"The Right-To-The-City Question" and Indigenous Urban Populations in Capital Cities in Cameroon. (March 2017) - Njoh, Ambe J
This paper explores the implications of state land tenure modernization and urbanization-promotion initiatives for human rights in Cameroon. The aim is to promote understanding of the implications of these initiatives for the right-to-the-city of indigenous urban residents. It is argued that the implications are more severe in politico-administrative headquarters than elsewhere in the country. Three different cities have served, at some point, as national politico-administrative headquarters in Cameroon, the study's empirical referent. The designation of any city as a politico-administrative headquarters invariably creates a land scarcity problem in that city. The problem is aggravated for the city's indigenous population by colonial and post-colonial planning policies. For this reason, the policies are said to be in violation of basic human rights as stipulated by the UN Declaration of Universal Human Rights as well as the African Charter.